2021
DOI: 10.1088/1361-6463/ac30ba
|View full text |Cite
|
Sign up to set email alerts
|

Critical study of partial discharge inception in voids: statistical behavior to stochastic nature

Abstract: Although many studies have been done and advanced progress has been made in understanding partial discharge (PD) behavior in the void, this is not the case firinception of PD, especially its stochastic nature. The statistical behaviors of PD inception voltage (PDIV) and inception time delay (PDTD) inside the void were investigated in this study through repeated tests to observe the stochastic nature of PD inception. The results show that the PDIV and PDTD of the void are highly dispersed and obey Weibull and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The shape parameter b describes the shape of the Weibull Curve. If the shape parameter b increases from 0, the curve will gradually change from a right deflection curve to a left deflection curve [34]. If altitude is 50 m, the shape parameter b is 2.00, and the Weibull Curve is a right deflection curve; the statistical time delay obeys the special case of Rayleigh Distribution, which is consistent with the conclusion of literature [18] in low altitude areas.…”
Section: Weibull Distribution Modelsupporting
confidence: 84%
See 2 more Smart Citations
“…The shape parameter b describes the shape of the Weibull Curve. If the shape parameter b increases from 0, the curve will gradually change from a right deflection curve to a left deflection curve [34]. If altitude is 50 m, the shape parameter b is 2.00, and the Weibull Curve is a right deflection curve; the statistical time delay obeys the special case of Rayleigh Distribution, which is consistent with the conclusion of literature [18] in low altitude areas.…”
Section: Weibull Distribution Modelsupporting
confidence: 84%
“…Weibull Distribution Model is a distribution model proposed by Weibull. W based on the theory of 'weakest-link', it is used to calculate system failure probability distribution including several links, and it is applicable to failure of one link can stop the whole system [32][33][34]. In the discharge gap, any effective electron generated in critical volume can start the streamer, which meets the applicable conditions of Weibull Distribution Model.…”
Section: Probability Distribution Characteristics Of Statistical Time...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that repetitive PDs in insulating materials can result in long-term damages since the released energy can cause a rapid heating and ultimately dielectric breakdown [21][22][23][24]. Measurements of PDs are commonly used in electrical engineering to assess the degradation and aging of high-voltage insulators [25][26][27][28][29], but the method has not yet been broadly adopted for ceramic materials [30][31][32][33][34]. In the context of flash sintering, PD measurements were recently shown to be an efficient method to characterize the quality and number of the electrode/sample contact areas when no Pt paste was used to sinter Y-stabilised zirconia (YSZ) above 250 • C [35].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, regarding the study on the degradation characteristics of OIP/OIPB due to bubble PD, Zhang Rui et al [15], [16] studied the degradation characteristics of OIP due to the continuous action of bubble PD between OIP layers, and they concluded that the mechanisms of OIP failure due to PD include direct failure and cumulative damage failure. The choice of mechanism depends on the evolutionary stage of PD and the conditions of the oil-paper insulation.…”
Section: Introductionmentioning
confidence: 99%